Power systems signal processing for smart grids - Ribeiro, Paulo F. (Chichester, West Sussex : John Wiley & Sons, 2014)
"With special relation to smart grids, this book provides clear and comprehensive explanation of how Digital Signal Processing (DSP) and Computational Intelligence (CI) techniques can be applied to solve problems in the power system. Its unique coverage bridges the gap between DSP, electrical power and energy engineering systems, showing many different techniques applied to typical and expected system conditions with practical power system examples. Surveying all recent advances on DSP for power systems, this book enables engineers and researchers to understand the current state of the art and to develop new tools. It presents: an overview on the power system and electric signals, with description of the basic concepts of DSP commonly found in power system problems the application of several signal processing tools to problems, looking at power signal estimation and decomposition, pattern recognition techniques, detection of the power system signal variations description of DSP in relation to measurements, power quality, monitoring, protection and control, and wide area monitoring a companion website with real signal data, several Matlab codes with examples, DSP scripts and samples of signals for further processing, understanding and analysis Practicing power systems engineers and utility engineers will find this book invaluable, as will researchers of electrical power and energy systems, postgraduate electrical engineering students, and staff at utility companies"--
4.8.1 Frequency Response of DFT Filter4.8.2 Asynchronous Sampling; 4.9 The z-Transform; 4.9.1 Rational z-Transforms; 4.9.2 Stability of Rational Transfer Function; 4.9.3 Some Common z-Transform Pairs; 4.9.4 z-Transform Properties; 4.10 Conclusions; References; 5 Basic Power Systems Signal Processing; 5.1 Introduction; 5.2 Linear and Time-Invariant Systems; 5.2.1 Frequency Response of LTI System; 5.2.2 Linear Phase FIR Filter; 5.3 Basic Digital System and Power System Applications; 5.3.1 Moving Average Systems: Application; 5.3.2 RMS Estimation.
Includes bibliographical references and index.
Print version record.
Keywords: Electric power systems; Signal processing -- Digital techniques; Smart power grids; Electric power systems; Signal processing -- Digital techniques; Smart power grids; TECHNOLOGY & ENGINEERING -- Signals & Signal Processing; Electric power systems; Signal processing -- Digital techniques; Smart power grids; Electronic books